2011
DOI: 10.4314/mmj.v23i2.70746
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive potential of some ‘edible’ soils in Blantyre city, Malawi

Abstract: BackgroundPregnant women in Malawi consume soil, but the nutritive potential of these soils is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Iron deficiency may be less prevalent in rural areas as rural residents have better access to diverse and more nutritious food sources; foods rich in iron such as eggs, leafy green vegetables and in our lake-shore population, fish; and fruits containing Vitamin C, enhancing iron absorption. Rural women may be more likely to access the mineral-rich clay pellets traditionally consumed during pregnancy [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Iron deficiency may be less prevalent in rural areas as rural residents have better access to diverse and more nutritious food sources; foods rich in iron such as eggs, leafy green vegetables and in our lake-shore population, fish; and fruits containing Vitamin C, enhancing iron absorption. Rural women may be more likely to access the mineral-rich clay pellets traditionally consumed during pregnancy [37]. …”
Section: Discussionmentioning
confidence: 99%
“…[50] reported that acidic geophagic materials are more preferred by pregnant women in Kenya, Malawi, South Africa, and Nigeria. The preference for acidic materials is traditionally accepted as capable of preventing excess saliva secretion and reducing nausea during pregnancy [51,52]. According to [53] slightly acidic geophagic materials aid in gastric juice neutralization.…”
Section: Resultsmentioning
confidence: 99%
“…Studied samples presented mean = 1744 mg/kg in sand, and 2837 mg/kg in silty fractions. Zinc is described as beneficial in several physiological activities, including synthesis and degradation of carbohydrates, proteins, lipids, and nucleic acids, as well as testicular maturation and wound healing [52]. Excessive and prolonged Zn intake can cause anemia and affect the immune system [79].…”
Section: Resultsmentioning
confidence: 99%
“…Geophagic materials are commonly consumed based on several reasons, including nutrients supplementation to compensate the deficiency of some essential elements such as Fe, Ca, Mg, Zn in the human diet (Kambunga et al, 2019a , 2019b ; Lakudzala & Khonje, 2011 ); medicinal properties used as remedy to cure some common illnesses in the gastrointestinal (GI) tract (e.g., diarrhoea and constipation) (Ekosse et al, 2017 ; Fosso-Kankeu et al, 2015 ); and to ease cravings and morning sicknesses as part of cultural and traditional beliefs among pregnant women (Kambunga et al, 2019a , 2019b ; Msibi, 2014 ).…”
Section: Introductionmentioning
confidence: 99%